Botticelli - Gebhart, Emile, 1839-1908 (Temporis collection., 2012)
The Medici court painter Botticelli is one of the unequivocal artists of the Italian Renaissance alongside Leonardo da Vinci, Michelangelo and Raphael. Favouring feminine portraits, Botticelli stands apart through the finesse of his lines and the unbridled sensuality of his paintings. Between religious and private commissions this Florentine artist introduced the profane into art through works of complex mythological subjects, such as the incontrovertibly masterful Primavera and The Birth of Venus, and knew how to delight the erudite patrons of art. The Madonna of the Magnificat remains one of.